Zoneamento geoambiental da área de proteção ambiental de Canoa Quebrada - Aracati - Ceará - Leal, José Reginaldo Lima Verde (2003)
The Environmental Protection Area (EPA) of Canoa Quebrada covering 6,334.75 hectares is located on Aracaty County, east coast of Ceará state, and 154 kilometers distant from Fortaleza. This EPA includes the following communities: Canoa Quebrada, Estevão, Beirada, Canavieira and Cumbe. In this region, the implantation of the EPA of Canoa Quebrada was accomplished by studies in order to get a better knowledge of the area and of the agents of littoral dynamics as, climate, wind, waves, currents, river flow, as well as vegetation and socio-economic aspects. The geo-environmental map was surveyed though photo-interpretation and field checking at scale 1: 25.000, where are still include the population; shrimp breeding tanks; the several kinds of vegetation; rivers and ponds; arrows indicating the dune advance direction and speed; sediment deposition and erosion, and graphic of direction for winds and waves. In this work for different environment were found: marine, aeolian, fluvio-marine and fluvial. In the first, we identified the beach (foreshore), berms, cliffs and beach rocks. In the environment dominated by the winds, individualized deflation plains, mobile and fastened by vegetation sand dunes and paleodunes fields. They composed the fluvio-marine plain mangrove, salgado and apicuns. And, finally, in the fluvial environment of Jaguaribe were going differentiated fluvial plain, the fluvial bars and island, besides the terraces. According to ecosystems classification of spatial structure, the terraces were considered transitional upland fringe; fluvial and fluvio-marine plains, floodplain; the river itself, island and fluvial bars, as belonging to stream channel. All of them form the steam corridor. The remaining of the landscape is composed of continuous areas (transgressive dunefields, deflation plain and beach) that are named matrix. The isolated areas as paleodunes, dunes fastened by vegetation, cliffs, berms and beach rocks are called patches. Inside the islands, the stains without constituting a continuous surface form a set denominated mosaic. In the planning and classification of use and occupation of land, the units of ecosystem were going framed, according IBAMA's legislation and route as: zone of permanent protection (beach, cliff, beach rocks, paleodune, mobile and fastened by vegetation sand dunes, ponds, rivers and mangrove); zone of special protection (salgados, apicuns and fluvial plain); priority preservation zone (deflation plain); and special preservation zone (terraces). Besides activities and interdictions suggestions for EPA of Canoa Quebrada four environmental programs were proposed for the Jaguaribe river: Navigation channel clearance; Construction of Collector and Submarine emissary; Definition of the Real Capacity of Estuary recovery; and Ecological stream flow, the minimum flow that had to have the Jaguaribe river for serf purification of the contaminating substances. This river is the most important ecosystem in the EPA of Canoa Quebrada. And, shrimp farms are from the environmental point of view the biggest problem by the synergy effect, due to the immense volume of aquaculture in proximities of the mangroves and using water from very narrow gamboas. It was proposed four environmental programs for Jaguaribe river: deobstruction of main channel; construction of collector and submarine emissary; definition of the estuary restoration real capacity; and determination of minimum streamflow to permit auto-depuration of the river Jaguaribe contaminants. Shrimp farms are greatest environment problem because of the excessive volume of aquaculture, next to mangroves using water from very narrows gamboas.